2020
DOI: 10.1016/j.vas.2020.100149
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endometritis on milk yield of zero-grazed dairy cows on smallholder farms in Rwanda

Abstract: Highlights The effect of endometritis disease on the milk yield among zero-grazed dairy cows on smallholder farms in rwanda were quantified. The daily milk yield of endometritis positive cows was 15.3% lower compared to endometritis negative cows. The estimated mean MY discarded was 51.4 ± 2.2 litres/cow with a median of 51.5 litres/cow. The percent of total MY loss was much higher (41.6%) among CLE positive cows that received treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…The present study quantified the effect of major diseases on productivity such as 305-milk yield, days open, culling rate, and death rate on a large Japanese dairy farm located in a temperate climate zone. Although negative effects of major diseases on the productivity in the present study agrees with previous studies conducted in cold zones [17,[21][22][23], our findings showing few interactions between disease status and calving season on productivity indicate that the negative effects of major diseases on productivity were independent of heat stress. Additionally, our results quantifying the effect of diseases on productivity on a large dairy farm, and those of our previous study investigating the prevalence and incidence rates of each disease on a large dairy farm [5], can be used to predict long-term herd productivity and help to ensure appropriate culling guidelines and practice are implemented on large dairy farms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study quantified the effect of major diseases on productivity such as 305-milk yield, days open, culling rate, and death rate on a large Japanese dairy farm located in a temperate climate zone. Although negative effects of major diseases on the productivity in the present study agrees with previous studies conducted in cold zones [17,[21][22][23], our findings showing few interactions between disease status and calving season on productivity indicate that the negative effects of major diseases on productivity were independent of heat stress. Additionally, our results quantifying the effect of diseases on productivity on a large dairy farm, and those of our previous study investigating the prevalence and incidence rates of each disease on a large dairy farm [5], can be used to predict long-term herd productivity and help to ensure appropriate culling guidelines and practice are implemented on large dairy farms.…”
Section: Discussionsupporting
confidence: 91%
“…In general, the effects of diseases on productivity have been investigated using single disease status. CM is known to have negative effects on productivity [13][14][15], and some Dairy 2022, 3 studies have shown that MD and PD also have negative effects on productivity [13,16,17]. However, previous studies discovered that the effect of disease on productivity differed between cows suffering from a single disease status and those suffering from multiple diseases status [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It was established that the subinvolution of the organs of the reproductive system in cows in the postpartum period occurred against the background of endometritis from 37.3% in the first department to 43.5% in the second department. Other researchers P. Nyabinwa et al (2020) indicate that postpartum endometritis is recorded at the level of 23.5% of the total number of cows that have calved, which leads to a decrease in productivity. Some authors, N. Pascal et al (2021), indicate that often endometritis occur in a complex with subinvolution of the uterus after delivery assistance and litter retention within 21-60 days after delivery.…”
Section: Table 5 Fertilization Of Cows During the Year In Experimenta...mentioning
confidence: 99%
“…In addition to reproduction, endometritis also has a negative impact on milk production 6 , 7 . A significant positive correlation between the prevalence of endometritis and reduced milk yield (15% reduction per day) has been demonstrated in zero-grazed dairy herds 8 . The resultant significantly longer calving intervals, low milk yields, and decreased reproductive efficiency drive up the culling rates in dairy herds 9 .…”
Section: Introductionmentioning
confidence: 95%